2006
DOI: 10.1021/es051694k
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effects of Free Nitrous Acid on the Energy Generation and Growth Processes of an Enriched Nitrobacter Culture

Abstract: The inhibitory effects of nitrite (NO2-)/free nitrous acid (HNO2-FNA) on the metabolism of Nitrobacter were investigated using a method allowing the decoupling of the growth and energy generation processes. A lab-scale sequencing batch reactor was operated forthe enrichment of a Nitrobacter culture. Fluorescent in situ hybridization (FISH) analysis showed that 73% of the bacterial population was Nitrobacter. Batch tests were carried out to assess the oxygen and nitrite consumption rates of the enriched culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
97
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 192 publications
(109 citation statements)
references
References 16 publications
(23 reference statements)
4
97
1
1
Order By: Relevance
“…Free nitrous acid (FNA), the protonated form of nitrite, was recently demonstrated to be the true metabolic inhibitor behind the usually observed nitrite inhibition (11). In recent treatment of sewer biofilms, it was seen that application of FNA for 6 to 24 h at 0.2 to 0.3 mg N/liter decreased the live cell percentage from about 80% to 5 to 15% (3).…”
mentioning
confidence: 99%
“…Free nitrous acid (FNA), the protonated form of nitrite, was recently demonstrated to be the true metabolic inhibitor behind the usually observed nitrite inhibition (11). In recent treatment of sewer biofilms, it was seen that application of FNA for 6 to 24 h at 0.2 to 0.3 mg N/liter decreased the live cell percentage from about 80% to 5 to 15% (3).…”
mentioning
confidence: 99%
“…It has been observed that high concentrations of nitrite can inhibit the nitrification process and that could be mainly related to the pH values through the formation of HNO 2 . Nitrous acid is known to inhibit nitrification, thus, low pH values must be avoided in nitrifying processes (Anthonisen et al, 1976;Vadivelu et al, 2006aVadivelu et al, , 2006b. Recently, Silva et al (2011) reported that the nitrite-oxidizing process was more sensitive to the presence of nitrite than the ammonium-oxidizing process, suggesting that nitrite accumulation in nitrification systems should be controlled to avoid a higher accumulation of nitrite and a decrease in nitrate yield.…”
Section: Environmental Factors Affecting Nitrificationmentioning
confidence: 99%
“…It has been reported that, at parts per billion (ppb) levels, FNA has inhibitory effects on: 1) the anabolic and catabolic activities of ammonia and nitrite oxidising bacteria [2,3]; 2) growth, nitrate and nitrite reduction activities of denitrifying bacteria in activated sludge [4] and 3) aerobic and anoxic phosphorus uptake by polyphosphate accumulating organisms [5,6]. In addition, FNA has also been shown to inhibit methanogens [7], pathogens [8] and yeast [9].…”
Section: Introductionmentioning
confidence: 99%